International Perspectives on Health and Safety Among Dairy Workers Challenges, Solutions and the Future - John Rosecrance (Frontiers Research Topics, 2018)
This e-book provides the insight into occupational health and safety problems, challenges and solutions of the dairy sector. Thirty-two authors have been sharing their results and knowledge reflecting the challenges from small scale farming up to industrial style. The worldwide trend of growing farm sizes and a reduction in numbers is one of the major drivers for the changes in the working environment. Musculoskeletal disorders are among the most prevalent health problems of people working on farms. Nevertheless mechanisation has not reduced the number of complaints, and new problems arise due to the changing working environment.